Mutant KRAS as a prognostic biomarker after hepatectomy for rectal cancer metastases: Does the primary disease site matter?. (20th October 2021) - Amini, Neda; Andreatos, Nikolaos; Margonis, Georgios Antonios; Buettner, Stefan; Wang, Jaeyun; Galjart, Boris; Wagner, Doris; Sasaki, Kazunari; Angelou, Anastasios; Sun, Jinger; Kamphues, Carsten; Beer, Andrea; et al.
Abstract: Background: The prognostic implication of mutant KRAS (m KRA S) among patients with primary disease in the rectum remains unknown. Methods: From 2000 to 2018, patients undergoing hepatectomy for colorectal liver metastases at 10 collaborating international institutions with documented KRAS status were surveyed. Results: A total of 834 (65.8%) patients with primary colon cancer and 434 (34.2%) patients with primary rectal cancer were included. In patients with primary colon cancer, mKRAS served as a reliable prognostic biomarker of poor overall survival (OS) (hazard ratio [HR]: 1.58, 95% CI 1.28‐1.95) in the multivariable analysis. Although a trend towards significance was noted, m KRAS was not found to be an independent predictor of OS in patients with primary rectal tumors (HR 1.34, 95% CI 0.98‐1.80). For colon cancer, the specific codon impacted in m KRAS appears to reflect underlying disease biology and oncologic outcomes, with codon 13 being associated with particularly poor OS in patients with left‐sided tumors (codon 12, HR 1.56, 95% CI 1.22‐1.99; codon 13, HR 2.10 95% CI 1.43‐3.08;). Stratifying the rectal patient population by codon mutation did not confer prognostic significance following hepatectomy. Conclusions: While the left‐sided colonic disease is frequently grouped with rectal disease, our analysis suggests that there exist fundamental biologic differences that drive disparate outcomes. Although there was a trend toward significance of KRAS mutations for patients with primary rectal cancers, it failed to achieve statistical significance. Abstract : Evaluating the outcomes of colorectal cancer liver metastases stratified by somatic KRAS status, Amini and colleagues found key differences according to the site of disease origin. Although KRAS mutation impacted prognosis among patients with colon tumors, it was not an independent predictor of prognosis in those with primary rectal tumors.